Toll-Like Receptors in the Pathogenesis of Autoimmune Diseases - Akbar Mohammad Hosseini; Jafar Majidi; Behzad Baradaran; Mehdi Yousefi (Tabriz University of Medical Sciences, 2015)
Human Toll-like receptors (TLRs) are a family of transmembrane receptors, which play a key role in both innate and adaptive immune responses. Beside of recognizing specific molecular patterns that associated with different types of pathogens, TLRs may also detect a number of self-proteins and endogenous nucleic acids. Activating TLRs lead to the heightened expression of various inflammatory genes, which have a protective role against infection. Data rising predominantly from human patients and animal models of autoimmune disease indicate that, inappropriate triggering of TLR pathways by exogenous or endogenous ligands may cause the initiation and/or perpetuation of autoimmune reactions and tissue damage. Given their important role in infectious and non-infectious disease process, TLRs and its signaling pathways emerge as appealing targets for therapeutics. In this review, we demonstrate how TLRs pathways could be involved in autoimmune disorders and their therapeutic application.